Preparation method, product and application of flower-shaped carbon-based Mn-doped NiCoP thin film electrode material
By preparing flower-shaped carbon-based Mn-doped NiCoP thin film electrode material using hydrothermal deposition method and gas-solid reaction method in supercapacitors, the problems of low energy density and weak electrochemical activity of nickel-cobalt phosphides in existing supercapacitors are solved, and the high specific capacitance and energy density are improved.
Patent Information
- Application Number
- CN202411363809.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-28
AI Technical Summary
The low energy density of existing supercapacitors limits its practical application, and nickel-cobalt phosphides have weak electrochemical activity and low conductivity in practical applications.
The flower-like carbon-based Mn-doped NiCoP thin film electrode material was prepared by hydrothermal deposition and gas-solid reaction method. The electrochemical activity and electron conductivity were enhanced by introducing three-dimensional walnut shells.
It realizes rapid transmission of electrons and efficient charge transfer, improves the specific capacitance and energy density of the electrode material, and has a high capacity retention rate after high cycle times.
Smart Images

Figure CN119218976B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical technology, and in particular relates to a preparation method, product and application of a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material. Background Art
[0002] With the rapid growth of energy demand, people pay more and more attention to green and sustainable energy such as solar energy, wind energy and tidal energy. However, in order to improve energy efficiency and solve the limitations of these emerging energy sources, people are increasingly aware of the importance of developing energy storage devices, such as batteries, fuel cells and supercapacitors (SCs). Supercapacitors have attracted widespread attention among many energy storage devices due to their high power density, fast charge and discharge capabilities, high safety and long cycle life. However, the low energy density severely limits the practical application of supercapacitors. Therefore, constructing suitable electrode materials is the key to achieving high-performance supercapacitors.
[0003] Bimetallic phosphides have been widely studied as electrode materials for supercapacitors due to their high theoretical specific capacity, electrical conductivity, and structural stability. However, the redox reactions of pseudocapacitive materials are mainly limited to the surface or near the surface, so the utilization rate of electrode materials is low. The key to solving this problem is to combine materials with large specific surface area and fast electron transfer speed, such as biomass carbon, graphene, and carbon nanotubes, with NiCoP to design a variety of composite electrode materials with unique composition and structural advantages, including nanoarrays, hollow nanostructures, and core-shell heterostructures. Huang et al. prepared a new type of multilayer carbon-coated NiCoP nanoparticles by calcination / phosphating method, and embedded these nanoparticles into nitrogen-doped carbon nanotubes (NiCoP / NCNTs). NiCoP / NCNTs has a high conductivity at 1.0 A·g -1 When the temperature is 1628.4F·g -1 However, single nickel-cobalt-based metal phosphides still exhibit weak electrochemical activity and low conductivity in practical applications. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a preparation method, product and application of a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material comprises the following steps: a three-dimensional walnut shell-derived porous carbon-based Mn-doped NiCo precursor is deposited on a growth substrate by a hydrothermal deposition method; and then the three-dimensional walnut shell-derived porous carbon-based Mn-doped NiCo precursor is phosphated by a gas-solid reaction method to obtain the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material (WSC-N / O@Mn-NiCoP).
[0008] The introduced heteroatoms will occupy certain host sites and modulate the band gap of the original phosphide. The resulting lattice defects will induce excellent electrical conductivity and fast ion transfer capability, further enhancing the electrochemical activity. In addition, the incorporation of heteroatoms will lead to changes in the microstructure of NiCoP, and the hierarchical structure is conducive to the penetration of electrolytes and enhances the electrochemical performance of NiCoP. Therefore, flower ball-shaped Mn-doped biomass carbon-based NiCoP composites were prepared by hydrothermal deposition and gas-solid reaction phosphating. The introduction of three-dimensional walnut shell-derived porous carbon (WSC-N / O) and the doping of Mn enhanced the electrochemical activity and electronic conductivity, thereby achieving fast electron transport.
[0009] Furthermore, a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material specifically comprises the following steps:
[0010] A manganese source, a cobalt source and a nickel source are dissolved in water, and three-dimensional walnut shell-derived porous carbon (WSC-N / O), ammonium fluoride (NH4F) and urea are added, and stirred until completely dissolved to obtain a mixed solution, and the mixed solution and a growth substrate are transferred to an autoclave for high-temperature treatment to obtain a carbon-based Mn-doped NiCo precursor;
[0011] The growth substrate carrying the carbon-based Mn-doped NiCo precursor and the phosphorus source are placed in a tubular furnace, and calcined after nitrogen is introduced, with the phosphorus source located upstream of the nitrogen. After the calcination, the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material is obtained.
[0012] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the growth substrate is nickel foam.
[0013] Furthermore, in a method for preparing a flower-like carbon-based Mn-doped NiCoP thin film electrode material, the three-dimensional walnut shell-derived porous carbon (WSC-N / O) is obtained by mixing walnut shell powder, 2-methylimidazole, sodium nitrate and alkali and then heating them.
[0014] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the mass ratio of the manganese source, cobalt source, nickel source and three-dimensional walnut shell-derived porous carbon is 3:3:3:1, and the mass ratio of the three-dimensional walnut shell-derived porous carbon, ammonium fluoride and urea is 10 mg:0.32 g:1.1 g.
[0015] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the high temperature treatment is performed at a temperature of 150° C. for 6 hours.
[0016] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the mass ratio of the carbon-based Mn-doped NiCo precursor to the phosphorus source is 1:3.
[0017] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the calcination temperature is 350° C., the holding time is 3 h, and the heating rate is 2° C. / min.
[0018] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the nitrogen is introduced for 10 minutes.
[0019] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the manganese source is MnCl2, the cobalt source is Co(NO3)2·6H2O, the nickel source is Ni(NO3)2·6H2O, and the phosphorus source is NaH2PO2.
[0020] The second technical solution of the present invention:
[0021] A flower-shaped carbon-based Mn-doped NiCoP thin film electrode material prepared by the preparation method.
[0022] The third technical solution of the present invention:
[0023] The application of the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material in the preparation of aqueous zinc ion batteries (ZIBs).
[0024] Compared with the prior art, the present invention has the following advantages and technical effects:
[0025] (1) The present invention introduces WSC-N / O and Mn elements during the preparation process of flower-like carbon-based Mn-doped NiCoP thin film electrode material (WSC-N / O@Mn-NiCoP). The introduction of WSC-N / O and the doping of Mn enhance the electrochemical activity and electronic conductivity, thereby achieving rapid electron transmission, ensuring efficient charge transfer, and enhancing the active surface area. As an electrode material, WSC-N / O@Mn-NiCoP has a high electrochemical performance at 5.0 A·g-1 The specific capacitance is 1460F·g -1 In addition, the WSC-N / O@Mn-NiCoP / / WSC-N / O (ASC) device prepared with WSC-N / O@Mn-NiCoP as the material was -1 The energy density is 69.1Wh·kg -1 , after 8000 cycles, the capacity retention rate of ASC was 85.8%.
[0026] (2) The present invention successfully prepared flower-like carbon-based Mn-doped NiCoP thin film electrode material (WSC-N / O@Mn-NiCoP) by hydrothermal deposition and gas-solid reaction method, and further used it in the preparation of high-performance supercapacitors and aqueous zinc-ion batteries. The application of WSC-N / O@Mn-NiCoP in aqueous zinc-ion batteries (ZIBs) was further verified. The results showed that at 750 W·Kg -1 When Zn / / WSC-N / O@Mn-NiCoP is used, the energy density is 148.9Wh·Kg -1 After 1000 cycles, the capacity retention rate is 80.6%. Therefore, the WSC-N / O@Mn-NiCoP of the present invention provides a new method for designing and manufacturing high-performance energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 This is a schematic diagram of the process for preparing the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material of the present invention;
[0029] Figure 2 X-ray diffraction (XRD) patterns of Example 1 (WSC-N / O@Mn-NiCoP), Comparative Example 1 (NiCoP) and Comparative Example 2 (Mn-NiCoP);
[0030] Figure 3 SEM images (a, b) and EDS mapping analysis results (c) of WSC-N / O@Mn-NiCoP prepared in Example 1;
[0031] Figure 4 XPS spectrum of WSC-N / O@Mn-NiCoP prepared in Example 1 (a) and high-resolution Ni 2p, Co2p, Mn 2p, P 2p and C 1s peak spectra (bf);
[0032] Figure 5The pore size distribution curves and N2 adsorption-desorption curves (a) and BET surface area and pore volume measurement results (b) of Example 1 (WSC-N / O@Mn-NiCoP), Comparative Example 1 (NiCoP) and Comparative Example 2 (Mn-NiCoP);
[0033] Figure 6 The results of Example 1 (WSC-N / O@Mn-NiCoP), Comparative Example 1 (NiCoP) and Comparative Example 2 (Mn-NiCoP) in a three-electrode system of aqueous zinc ion batteries (ZIBs) at 20 mV·s -1 CV curves of WSC-N / O@Mn-NiCoP electrode at different scan rates (a), CV curves of WSC-N / O@Mn-NiCoP electrode at 1.0 A·g -1 GCD curves of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP electrodes at different current densities (c), GCD curves of WSC-N / O@Mn-NiCoP electrodes at different current densities (d), specific capacitances of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP electrodes at different current densities (e), ion / electron diffusion kinetics of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP electrodes in the range of 0.01 Hz to 10 kHz (f);
[0034] Figure 7 Schematic diagram of energy storage of ASC device (a), CV curves of ASC device under different electrochemical windows (b), ASC device at 5mV·s -1 -100V·s -1 CV curves at scan rate (c), GCD curves of ASC device at different current densities (d), specific capacitance of ASC device at different current densities (e), Ragone plot of ASC device (f). DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] The embodiment of the present invention provides a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material (see the schematic diagram of the preparation process Figure 1 ), a three-dimensional walnut shell-derived porous carbon-based Mn-doped NiCo precursor is deposited on a growth substrate by a hydrothermal deposition method, and then the three-dimensional walnut shell-derived porous carbon-based Mn-doped NiCo precursor is phosphated by a gas-solid reaction method to obtain the flower-like carbon-based Mn-doped NiCoP thin film electrode material (WSC-N / O@Mn-NiCoP), which more specifically includes the following steps:
[0041] A manganese source, a cobalt source and a nickel source are dissolved in water, and three-dimensional walnut shell-derived porous carbon (WSC-N / O), ammonium fluoride (NH4F) and urea are added, and stirred until completely dissolved to obtain a mixed solution, and the mixed solution and a growth substrate are transferred to an autoclave for high-temperature treatment to obtain a carbon-based Mn-doped NiCo precursor;
[0042] The growth substrate carrying the carbon-based Mn-doped NiCo precursor and the phosphorus source are placed in a tubular furnace, and calcined after nitrogen is introduced, with the phosphorus source located upstream of the nitrogen. After the calcination, the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material is obtained.
[0043] In a preferred embodiment of the present invention, the growth substrate is nickel foam, and the mixed solution and two growth substrates are transferred to an autoclave.
[0044] In a preferred embodiment of the present invention, the three-dimensional walnut shell derived porous carbon (WSC-N / O) is obtained by mixing walnut shell powder, 2-methylimidazole, sodium nitrate and alkali and then heating. More specifically, the specific preparation method of the three-dimensional walnut shell derived porous carbon (WSC-N / O) used in the embodiment of the present invention is:
[0045] Walnut shell powder is mixed with 2-methylimidazole (C4H6N2), sodium nitrate (NaNO3), and potassium hydroxide (KOH) in a mass ratio of 2:2:1:6, and then the mixture is heated to 900°C in a tube furnace under a nitrogen atmosphere at a heating rate of 5°C / min. The obtained black sample is washed with 2M hydrochloric acid, deionized water and ethanol for a total of 2 times, and then dried at 60°C to obtain the three-dimensional walnut shell derived porous carbon (WSC-N / O).
[0046] The unique flower-ball-like structure of WSC-N / O successfully prevents the separation and aggregation of Mn-NiCoP nanoparticles, while providing a larger surface area for electrolyte contact and facilitating ion transport.
[0047] In a preferred embodiment of the present invention, the mass ratio of the manganese source, cobalt source, nickel source and three-dimensional walnut shell derived porous carbon is 3:3:3:1, and the mass ratio of the three-dimensional walnut shell derived porous carbon, ammonium fluoride and urea is 10mg:0.32g:1.1g.
[0048] Changes in the amount of manganese source, cobalt source, and nickel source will result in the inability to synthesize the target product. Too much or too little carbon source will be detrimental to the formation of a special flower-like structure. The amount of ammonium fluoride and urea added is positively correlated with the carbon source, and mainly plays a bonding role.
[0049] In a preferred embodiment of the present invention, the temperature of the high temperature treatment is 150° C. and the time is 6 hours.
[0050] During the high-temperature treatment process, too low temperature and too short time are not conducive to precursor deposition, while too high temperature and too long time are not conducive to energy saving and environmental protection. More seriously, it will lead to excessive deposition of sediments, which is not conducive to structure formation.
[0051] Furthermore, in a method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, the mass ratio of the carbon-based Mn-doped NiCo precursor to the phosphorus source is 1:3.
[0052] Too much phosphorus source will aggravate the fragmentation of nickel foam, while too little will result in incomplete phosphating.
[0053] In a preferred embodiment of the present invention, the calcination temperature is 350° C., the holding time is 3 h, and the heating rate is 2° C. / min.
[0054] If the calcination temperature is too low and the time is too short, the phosphorus source will not be completely decomposed. If the temperature is too high and the time is too long, the nickel foam will be easily broken.
[0055] In a preferred embodiment of the present invention, the nitrogen is introduced for 10 minutes.
[0056] In a preferred embodiment of the present invention, the manganese source is MnCl2, the cobalt source is Co(NO3)2·6H2O, the nickel source is Ni(NO3)2·6H2O, and the phosphorus source is NaH2PO2.
[0057] The embodiment of the present invention also provides a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material prepared by the preparation method.
[0058] The raw materials used in the embodiments of the present invention are all commercially available.
[0059] The technical solution of the present invention is further illustrated by the following embodiments.
[0060] Example 1
[0061] MnCl2, Co(NO3)2·6H2O and Ni(NO3)2·6H2O were mixed in 50 mL of deionized water in a mass ratio of 1:1:1, and then 10 mg WSC-N / O, 0.32 g NH4F and 1.1 g urea were added, wherein the mass ratio of manganese source, cobalt source, nickel source and three-dimensional walnut shell-derived porous carbon was 3:3:3:1, and stirred until completely dissolved to obtain a mixed solution, and the obtained mixed solution and two pieces of nickel foam (1 cm×2 cm) were transferred to an autoclave and treated at 150°C for 6 h to obtain a carbon-based Mn-doped NiCo precursor;
[0062] The carbon-based Mn-doped NiCo precursor deposited on nickel foam and nickel foam are placed at one end of the porcelain boat, and NaH2PO2 is placed at the other end. The mass ratio of NaH2PO2 to the precursor is 3:1. Then the porcelain boat is placed in a tubular furnace, nitrogen is introduced, and the part containing NaH2PO2 is placed upstream of the nitrogen. The nitrogen needs to flow for 10 minutes. Then, the tubular furnace is heated to 350°C at a heating rate of 2°C / min for calcination and maintained for 3h. After the calcination treatment, a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material (WSC-N / O@Mn-NiCoP) is obtained.
[0063] Comparative Example 1
[0064] Co(NO3)2·6H2O and Ni(NO3)2·6H2O were mixed in 50 mL of deionized water at a mass ratio of 1:1, and then 0.32 g of NH4F and 1.1 g of urea were added and stirred until completely dissolved to obtain a mixed solution. The obtained mixed solution and two pieces of nickel foam (1 cm×2 cm) were transferred to an autoclave and subjected to high temperature treatment at 150°C for 6 h to obtain a NiCo precursor;
[0065] The NiCo precursor and nickel foam deposited on the nickel foam are placed at one end of the porcelain boat, and NaH2PO2 is placed at the other end. The mass ratio of NaH2PO2 to the precursor is 3:1. The porcelain boat is then placed in a tubular furnace, nitrogen is introduced, and the part containing NaH2PO2 is placed upstream of the nitrogen. The nitrogen needs to flow for 10 minutes. Then, the tubular furnace is heated to 350°C at a heating rate of 2°C / min for calcination and maintained for 3 hours. After the calcination treatment, the NiCoP thin film electrode material (NiCoP) is obtained.
[0066] Comparative Example 2
[0067] MnCl2, Co(NO3)2·6H2O and Ni(NO3)2·6H2O were mixed in 50 mL of deionized water at a mass ratio of 1:1:1, and then 0.32 g of NH4F and 1.1 g of urea were added and stirred until completely dissolved to obtain a mixed solution. The obtained mixed solution and two pieces of nickel foam (1 cm×2 cm) were transferred to an autoclave and treated at 150°C for 6 h to obtain a Mn-doped NiCo precursor.
[0068] The Mn-doped NiCo precursor deposited on nickel foam and nickel foam are placed at one end of the porcelain boat, and NaH2PO2 is placed at the other end. The mass ratio of NaH2PO2 to the precursor is 3:1. The porcelain boat is then placed in a tubular furnace, nitrogen is introduced, and the part containing NaH2PO2 is placed upstream of the nitrogen. The nitrogen needs to flow for 10 minutes. Then, the tubular furnace is heated to 350°C at a heating rate of 2°C / min for calcination and maintained for 3 hours. After the calcination treatment, a Mn-doped NiCoP thin film electrode material (Mn-NiCoP) is obtained.
[0069] Performance Testing
[0070] (1) X-ray diffraction (XRD) analysis
[0071] The X-ray diffraction (XRD) patterns of Example 1 (WSC-N / O@Mn-NiCoP), Comparative Example 1 (NiCoP) and Comparative Example 2 (Mn-NiCoP) are shown in Figure 2 , it can be seen that WSC-N / O@Mn-NiCoP exhibits the characteristic peak of NiCoP corresponding to PDF#71-2336 and the (002) plane of WSC-N / O located at 23°. In addition, Mn doping and WSC-N / O do not destroy the structure of NiCoP.
[0072] (2) SEM and EDS analysis
[0073] The SEM image of WSC-N / O@Mn-NiCoP prepared in Example 1 is shown in Figure 3 a and b in the figure reveal the presence of irregular spherical particles. Mn-NiCoP nanoparticles are evenly distributed in the porous carbon matrix of WSC-N / O. The unique flower-shaped structure successfully prevents the separation and aggregation of Mn-NiCoP nanoparticles, while providing a larger surface area for electrolyte contact and promoting ion transport. In addition, EDS mapping analysis was performed on WSC-N / O@Mn-NiCoP to analyze the distribution of Co, Ni, P, C and O elements ( Figure 3 (c), confirming the uniform distribution of these elements on WSC-N / O@Mn-NiCoP.
[0074] (3) X-ray photoelectron spectroscopy (XPS) analysis
[0075] The XPS spectrum of WSC-N / O@Mn-NiCoP prepared in Example 1 is shown in Figure 4 a, and the high-resolution Ni 2p, Co 2p, Mn 2p, P 2p, and C 1s peak spectra of WSC-N / O@Mn-NiCoP are shown in Figure 4 bf in. Figure 4 a Characterization of the surface chemical state and elemental composition of WSC-N / O@Mn-NiCoP, Ni 2p spectrum ( Figure 4 b) At 856.4 eV (Ni 2p 3 / 2 ) and 874.7eV(Ni 2p 1 / 2 ) corresponds to Ni 2+ The peaks at 853.2 eV and 870.6 eV, as well as the Ni-P peaks at 853.2 eV and 870.6 eV, indicate the presence of Ni 3+ Two satellite peaks at 862.4eV and 880.2eV were also determined. Co 2p spectrum ( Figure 4 The peaks of c) are located at 797 eV (Co 2p1 / 2), 783.6 eV (Co 2p3 / 2), and 778.4 eV, corresponding to Co 2+ 、Co 3+ and Co-P, and satellite peaks of Co 2p at 805eV and 786eV were also observed. The Mn 2p spectrum was also simulated ( Figure 4 d), peaks appear at 654.6 eV (Mn 2p1 / 2), 643.2 eV (Mn 2p3 / 2), and 647.8 eV (satellite peak), confirming that Mn in WSC-N / O@Mn-NiCoP 2+ and Mn 3+ The high-resolution P 2p spectrum peaks at 134.5 eV and 129.5 eV are assigned to typical phosphide materials and metal phosphides ( Figure 4 e). High-resolution C1s spectrum ( Figure 4f) shows three peaks, which are attributed to CC (284.3 eV), CO (285.7 eV), and CN (284.8 eV). Overall, these results confirm the successful preparation of WSC-N / O@Mn-NiCoP.
[0076] (4) Surface area and pore size distribution determination
[0077] The pore size distribution curves and N2 adsorption-desorption curves (inset) of Example 1 (WSC-N / O@Mn-NiCoP), Comparative Example 1 (NiCoP) and Comparative Example 2 (Mn-NiCoP) are shown in Figure 5 a in the figure, BET surface area and pore volume determination results are shown in Figure 5 b. It can be seen that in the range of 0.8-1.0P / P0, NiCoP and Mn-NiCoP exhibit significant hysteresis loops in the N2 adsorption-desorption isotherms, indicating the presence of many mesopores. In contrast, WSC-N / O@Mn-NiCoP shows a type I isotherm, which indicates the presence of many micropores, which can be attributed to the biomass-derived carbon WSC-N / O with abundant pores. According to the pore size distribution analysis, the pore size distribution of WSC-N / O@Mn-NiCoP is around 20nm, indicating that the composite material has abundant multi-level pores. In addition, the Brunauer-Emmett-Teller (BET) surface areas of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP were measured, which were 2.77m 2 ·g -1 、6.19m 2 ·g -1 and 15.02m 2 ·g -1 ( Figure 5 b).
[0078] Application Example 1
[0079] In order to evaluate the practical application potential of the prepared electrode materials, the electrochemical properties of the electrodes of Example 1 (WSC-N / O@Mn-NiCoP), Comparative Example 1 (NiCoP) and Comparative Example 2 (Mn-NiCoP) were characterized in an aqueous zinc ion battery (ZIBs) three-electrode system.
[0080] Figure 6 a Comparison of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP electrodes at 20 mV·s -1From the CV curves below, it can be seen that the CV curve area and peak current of WSC-N / O@Mn-NiCoP are the largest, showing excellent electrochemical performance. This is mainly due to the fact that Mn doping and heterogeneous structure optimize the charge transfer channel of WSC-N / O@Mn-NiCoP and accelerate the charge transfer rate. Figure 6 As shown in b, at different scan rates (5-100 mV·s -1 ), redox peaks can be observed in the CV curves of the WSC-N / O@Mn-NiCoP electrode, which confirms the Faradaic pseudocapacitive characteristics of WSC-N / O@Mn-NiCoP. Figure 6 c, at 1.0A·g -1 The GCD curves of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP electrodes are compared below, showing that the WSC-N / O@Mn-NiCoP electrode has the longest discharge time. Figure 6 d is the GCD curve of WSC-N / O@Mn-NiCoP electrode at different current densities. It can be seen that the charge and discharge curves of WSC-N / O@Mn-NiCoP electrode are almost symmetrical at different current densities, which means that the electrode material has excellent reversible performance and Coulomb efficiency.
[0081] Figure 6 e shows the specific capacitance of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP electrodes at different current densities. When the current density is 0.5 A·g -1 When the specific capacitance of WSC-N / O@Mn-NiCoP electrode is 1860F·g -1 , while the specific capacitances of NiCoP and Mn-NiCoP electrodes are 604 F·g -1 and 675F·g -1 When the current density increases to 5.0A·g -1 When the specific capacitance of WSC-N / O@Mn-NiCoP electrode is 1260F·g -1 The specific capacitances of NiCoP and Mn-NiCoP electrodes are 480 F·g -1 and 560F·g -1 , indicating that the WSC-N / O@Mn-NiCoP electrode exhibits higher capacity and excellent rate capability, which can be attributed to the synergistic effect between Mn-NiCoP with fast Faradaic reaction and highly conductive porous carbon (WSC-N / O), which accelerates the transport of ions and electrons.
[0082] Electrochemical impedance spectroscopy (EIS) is one of the most important criteria for measuring electrode reaction kinetics. The ion / electron diffusion kinetics of NiCoP, Mn-NiCoP and WSC-N / O@Mn-NiCoP electrodes in the range of 0.01 Hz to 10 kHz are shown in Figure 2. Figure 6 As shown in Fig. 5a, it can be seen that the equivalent series resistance (Rs) can be expressed as the intercept on the x-axis. The results show that the WSC-N / O@Mn-NiCoP electrode exhibits the smallest charge transfer resistance (Rct) and equivalent series resistance (Rs) among the three electrodes due to the enhanced conductivity of NiCoP by Mn doping and the introduction of porous carbon WSC-N / O. Secondly, the slope of the WSC-N / O@Mn-NiCoP electrode is the largest, indicating that the diffusion rate of ions in the electrode is faster.
[0083] Application Example 2
[0084] The WSC-N / O@Mn-NiCoP of Example 1 was prepared into a WSC-N / O@Mn-NiCoP / / WSC-N / O (ASC) device. The energy storage diagram of the ASC device is shown in Figure 7 a in Figure 7 b is the CV curve of the ASC device under different electrochemical windows. It can be seen that with the increase of potential, the CV curve of ASC becomes sharper, which is caused by electrode polarization. Therefore, it is more appropriate to choose 0-1.5V as the electrochemical test window. Figure 7 c shows the ASC device at 5 mV·s -1 -100V·s -1 From the CV curves at different scan rates, it can be seen that the redox peak of the device gradually shifts with the increase in scan rate. This is due to the increase in double-layer charge current density caused by the increase in scan rate. At 0-1.5V, the GCD curves of the ASC device at different current densities are shown in Figure 2. Figure 7 d, the specific capacitance of the ASC device at different current densities is calculated as Figure 7 As shown in e, it can be seen that the ASC device has a good specific capacitance (140F·g -1 , 1.0A·g -1 ), which is consistent with the result of CV. Figure 7 The Ragone diagram of the ASC device shown in f can reflect the relationship between the energy density and power density of the device. The results show that the ASC device has a maximum energy density of 69.1Wh kg -1 375W·kg -1 power density.
[0085] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a flower-shaped carbon-based Mn-doped NiCoP thin film electrode material, characterized in that: A three-dimensional walnut shell-derived porous carbon-based Mn-doped NiCo precursor is prepared by deposition on a growth substrate by a hydrothermal deposition method, and then the three-dimensional walnut shell-derived porous carbon-based Mn-doped NiCo precursor is phosphated by a gas-solid reaction method to obtain the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material; specifically comprising the following steps: A manganese source, a cobalt source and a nickel source are dissolved in water, and three-dimensional walnut shell-derived porous carbon, ammonium fluoride and urea are added, and stirred until completely dissolved to obtain a mixed solution, and the mixed solution and a growth substrate are transferred to an autoclave for high-temperature treatment to obtain a carbon-based Mn-doped NiCo precursor; Placing a growth substrate carrying a carbon-based Mn-doped NiCo precursor and a phosphorus source in a tube furnace, introducing nitrogen and calcining the substrate, wherein the phosphorus source is located upstream of the nitrogen, and obtaining the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material after calcination; The mass ratio of the manganese source, the cobalt source, the nickel source and the three-dimensional walnut shell-derived porous carbon is 3:3:3:1, and the mass ratio of the three-dimensional walnut shell-derived porous carbon, ammonium fluoride and urea is 10 mg: 0.32 g: 1.1 g; The mass ratio of the carbon-based Mn-doped NiCo precursor to the phosphorus source is 1:
3.
2. The method for preparing the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material according to claim 1, characterized in that: The temperature of the high temperature treatment is 150° C. and the time is 6 hours.
3. The method for preparing the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material according to claim 1, characterized in that: The calcination temperature is 350° C., the holding time is 3 h, and the heating rate is 2° C. / min.
4. The method for preparing the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material according to claim 1, characterized in that: The nitrogen gas introduction time is 10 min.
5. The method for preparing the flower-shaped carbon-based Mn-doped NiCoP thin film electrode material according to claim 1, characterized in that: The manganese source is MnCl2, the cobalt source is Co(NO3)2·6H2O, the nickel source is Ni(NO3)2·6H2O, and the phosphorus source is NaH2PO2.
6. A flower-shaped carbon-based Mn-doped NiCoP thin film electrode material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the flower-like carbon-based Mn-doped NiCoP thin film electrode material as claimed in claim 6 in the preparation of aqueous zinc ion batteries.
Citation Information
Patent Citations
Nano flower-shaped NiCoP supercapacitor electrode material, preparation method and application thereof
CN111446087A
N-doped porous carbon coated Mn-Co-Ni oxide core-shell structure electrode material and preparation method and application thereof
CN114497473A